Development of a mechanical maintenance training simulator in OpenSimulator for F-16 aircraft engines - Pinheiro, André (2014)
Mechanical maintenance of F-16 engines is carried out as a team effort involving 3–4 skilled engine technicians, but the details of its procedures and requisites change constantly, to improve safety, optimize resources, and respond to knowledge learned from field outcomes. This provides a challenge for development of training simulators, since simulated actions risk becoming obsolete rapidly and require costly reimplementation. This paper presents the development of a 3D mechanical maintenance training simulator for this context, using a low-cost simulation platform and a software architecture that separates simulation control from simulation visualization, in view of enabling more agile adaptation of simulators. This specific simulator aims to enable technician training to be enhanced with cooperation and context prior to the training phase with actual physical engines. We provide data in support of the feasibility of this approach, describing the requirements that were identified with the Portuguese Air Force, the overall software architecture of the system, the current stage of the prototype, and the outcomes of the first field tests with users.